Intervenções governamentais no mercado de crédito bancário brasileiro: bancos públicos e bancos privados varejistas competem entre si? - Torres, Sarah Amorim (2016)
This study investigates the existence of competition between retail government-owned and private banks in the event of federal government interventions imposed on the Brazilian bank lending market, such as the expansion of bank credit through the hike of public banks’ lending supply and the campaign aiming to reduce the banks’ spread levels led by state-owned banks. The Diff-in-Diff model predicts that public banks show higher loan growth, non-performing loans, lending returns, operational returns and cost of funding compared to private peers after the treatment. In addition, it finds evidence of differences in the asset allocation decisions of banks, as private banks preferred an asset portfolio with a higher proportion of liquid assets holdings and less loans compared to public banks after the treatment. These findings suggest that government-owned retail banks do not compete with private peers when their objective function is not only to maximize profits given risk.